A rare case of ectopic retrosternal goiter. Issue 4 (14th December 2020) - Oh, Shen Leong; Chia, Clement L. K.; Ooi, Oon Cheong; Sonawane, Vikram; Rao, Anil D.; Singaporewalla, Reyaz
Abstract: It is important for the clinician to be familiar with interpreting a variety of radiological modalities that provide vital information that will aid in the preoperative planning, counseling, and subsequent management of patients with retrosternal goiter. Abstract : It is important for the clinician to be familiar with interpreting a variety of radiological modalities that provide vital information that will aid in the preoperative planning, counseling, and subsequent management of patients with retrosternal goiter.